ANALISIS TINGKAT KEPUASAN MAHASISWA TERHADAP PROSES PEMBELAJARAN DAN KUALITAS LAYANAN AKADEMIK MASA PANDEMI COVID-19 - Rapmaida Megawaty Pangaribuan; Keristina Br Ginting (JURNAL DIFERENSIAL, 2021)
Online learning activities and academic services are the right methods during the Pandemic of Covid-19. The success of the implementation of activities in the network is said to be going well, one of which can be seen from the level of satisfaction of service recipients. However, based on the results of the researcher's observations, there were complaints that indicated dissatisfaction with the online learning process and academic services. The purpose of this study was to determine the level of satisfaction of the students of the Faculty of Science and Engineering, University of Nusa Cendana on the learning process and academic services by using a Likert scale model questionnaire instrument. There are five indicators used in this study, namely: tangibles (lecture tools, learning media and educational infrastructure), reliability (reliability of lecturers and academic staff), responsiveness, assurance (assurance of certainty) and empathy. By using the statistical data analysis show that in general students of the Faculty of Science and Engineering, University of Nusa Cendana are satisfied with the learning process and academic services with an average score of 3.78 for student choices and the average percent of respondents' achievement level (TCR) is 75.65%. If analyzed on a per item basis, there are 2 items that are already in the very satisfactory category and there are still 5 items that are in the quite satisfactory category, so that items that are still in the quite satisfactory category still need to be improved.